2016
DOI: 10.1002/chem.201602791
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Alkane C−H Alkoxycarbonylation

Abstract: Directly utilizing a chemical feedstock to construct valuable compounds is an attractive prospect in organic synthesis. In particular, the combination of C(sp(3) )-H activation and oxidative carbonylation involving alkanes and CO gas is a promising and efficient method to synthesize carbonyl derivatives. However, due to the high C-H bond dissociation energy and low polarity of unactivated alkanes, the carbonylation of unactivated C(sp(3) )-H bonds still remains a great challenge. In this work, we introduce a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…This will be further confirmed using the FESEM micrographs. It is worth to mention that the highly crystalline of -Al2O3 can be formed at 1000 °C, it is lower than the reported temperatures using similar combustion agent of citric acid [1,14,18]. The FESEM micrographs of the synthesized Al2O3 are given in Figure 2.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…This will be further confirmed using the FESEM micrographs. It is worth to mention that the highly crystalline of -Al2O3 can be formed at 1000 °C, it is lower than the reported temperatures using similar combustion agent of citric acid [1,14,18]. The FESEM micrographs of the synthesized Al2O3 are given in Figure 2.…”
Section: Resultsmentioning
confidence: 84%
“…At temperature range of 500 °C and 700 °C, the -Al2O3 material was formed [5,6], the annealing at 750 °C exhibited the Al2O3 [7], and the Al2O3 were formed between 900 °C and 1000 °C [6,8]. The stable -Al2O3 can be formed at 1100 °C and above [1,5,9].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently,L ei et al reported as imple and efficient method for constructing alkyl esters from simple alkanesa nd alcohols (Scheme 1), whichp rovides an ovel radical process for ester synthesis. [19] However,t he detailed mechanism of this radical carbonylation reaction, asw ell as as eries of radical-radical coupling reactions, still remains unclear. [20] As eries of radical generationsa nd conversions occur in this pathway.H owever, the capture, stabilization, and release of radicali ntermediates by transition-metal catalysts have been seldom investigated in other reports.…”
Section: Introductionmentioning
confidence: 99%